Effect of Cooperative Membership on Alleviating Problems of Flood Victims in Anambra State (A Study of Selected Cooperative in Ogbaru Local Government Area of Anambra State, Nigeria) - Okafor, Ogochukwu Esther; Chioma, Ngene Ngozi; Pethronila, Okafor Ifeoma (European Journal of Applied Sciences, 2022)
The regular annual flooding that destroys farmer’s crops in the studied area necessitated this study to examine the effect of cooperative membership on alleviating problems of flood victims in Anambra state, Nigeria. The work is anchored on the theory of vulnerability as derived from the ideas of Martha Albertson Fineman (2008). The study adopted a survey research design and the study area was Ogbaru local government Area of Anambra state. A sample of 100 members of agricultural cooperatives were selected through random sampling. Questionnaire was employed to obtain data for the study. Data were analyzed using descriptive and inferential statistics and hypotheses were tested at a 0.05 level of significance, signifying a 95% level of confidence. Findings revealed that the significant factor accounting for differences in their alleviation of problems were proved by being member of cooperative. The rate of alleviation of problems of cooperative members was extremely higher than that of non-cooperative; cooperative had more stable measures of mitigating problems for the development of rural farmers. The hypotheses revealed that of 0.793 shows that 79.3% of variations in income is caused by severity of flooding. The T-value of 0.000 is significant at 5% level showing the strength of the model. Severity of flooding have coefficient of -0.892 and was very significant. It shows that when flooding increase by one unit, income will fall by 0.892. in the studied area. Sequel to this, it was concluded that Being member of a cooperative society was discovered to be a better alternative for alleviation of the problems of flood victims in the area. It was recommended among others that important to give flood victims important needed information and enlightenment as regards flood events and insurance (of crops, livestock, farmlands and properties